Fuzzy Logic-Based SBR Acceleration Approach for Radio Propagation Prediction in Indoor Environments - Yildirim, Gungor; Gunduzalp, Emrullah; Tatar, Yetkin (Springer Heidelberg, 2022)
Radio propagation predictions play an important role in the design and installation of infrastructure systems that use radio communication technologies. Although different methods are used for this purpose, ray-tracing methods such as shooting and bouncing ray have proven to be successful in terms of performance. On the other hand, unnecessary ray tracing that consumes the system resources poses a serious problem in shooting and bouncing ray simulations. In the literature, geometric or hardware-based acceleration techniques have been generally recommended for making the simulations with optimum ray tracing in indoor environments. These methods bring along dependency on environment geometry, pre-processing, cost, and coding complexities. In this study, unlike the other methods, an approach that considers the ray characteristics, not the indoor environment geometry, and performs the unnecessary ray elimination using fuzzy logic has been proposed. The results of the proposed approach have been compared with the real measurements performed in three different real indoor environments and the results of traditional shooting and bouncing ray simulations. Also, this study will present the theoretical and mathematical details of the basic principles used in shooting and bouncing ray simulations and thus serve as a reference for the researchers who want to study this field.
Keywords: Ray tracing; Radio propagation; Shooting and bouncing ray; Fuzzy logic